Target organ expression and biomarker characterization of chemokine CCL21 in systemic sclerosis associated pulmonary arterial hypertension - Didriksen, Henriette; Molberg, Øyvind; Mehta, Adi; Jordan, Suzana; Palchevskiy, Vyacheslav; Fretheim, Håvard; Gude, Einar; Ueland, Thor; Brunborg, Cathrine; Garen, Torhild; Midtvedt, Øyvind; Andreassen, Arne K.; et al. (Frontiers in Immunology, 2022)
Introduction: Systemic sclerosis (SSc) is a heterogenous disorder that appears to result from interplay between vascular pathologies, tissue fibrosis and immune processes, with evidence for deregulation of chemokines, which normally control immune trafficking. We recently identified altered levels of chemokine CCL21 in SSc associated pulmonary arterial hypertension (PAH). Here, we aimed to define target organ expression and biomarker characteristics of CCL21. Materials and Methods: To investigate target organ expression of CCL21, we performed immunohistochemistry (IHC) on explanted lung tissues from SSc-PAH patients. We assessed serum levels of CCL21 by ELISA and Luminex in two well-characterized SSc cohorts from Oslo (OUH, n=552) and Zurich (n=93) University hospitals and in 168 healthy controls. For detection of anti-CCl21 antibodies, we performed protein array analysis applying serum samples from SSc patients (n=300) and healthy controls. To characterize circulating CCL21 in SSc, we applied immunoprecipitation (IP) with antibodies detecting both full length and tailless and a custom made antibody detecting only the C-terminal of CCL21. IP products were analyzed by SDS-PAGE/western blot and Mass spectrometry (MS). Results: By IHC, we found that CCL21 was mainly expressed in the airway epithelial cells of SSc patients with PAH. In the analysis of serum levels of CCL21 we found weak correlation between Luminex and ELISA (r=0.515, p<0.001). Serum levels of anti-CCL21 antibodies were higher in SSc patients than in healthy controls (p<0.001), but only 5% of the SSc population were positive for anti-CCL21 antibodies in SSc, and we found no correlation between anti-CCl21 and serum levels of CCL21. By MS, we only identified peptides located within amino acid (aa) 23-102 of CCL21, indicating that CCL21 in SSc circulate as a truncated protein without the C-terminal tail. Conclusion: This study demonstrates expression of CCL21 in epithelial lung tissue from SSc patients with PAH, and indicate that CCL21 in SSc circulates as a truncated protein. We extend previous observations indicating biomarker potential of CCL21, but find that Luminex is not suitable as platform for biomarker analyses. Finally, in vivo generated anti-CCL21 antibodies exist in SSc, but do not appear to modify serum CCL21 levels in patients with SSc-PAH.